Social Values and Social Norms - Berdikulova Surayyo Aslamovna; Jamalova Nargiza Ulugbek kizi (Periodica Journal, 2023)
Behavioral elements - social values and norms - are of the greatest interest to sociology. They largely determine not only the nature of people's relationships, their moral orientations, behavior, but also the very spirit of society as a whole, its uniqueness and difference from other societies.
Keywords: values; norms; development